A combined digital and organizational approach dramatically improves access to outpatient care in cardiology. (25th November 2020) - Jamal, F; Boiron, F; Tettoni, C; Couvert, I; Ielissof, C; Fasciani, S; Zebrowski, P.A; Dussardier, F; Schloter, N; Amaral, A
Abstract:  : We have previously shown that digital preconsultation saves medical time and may improve outcome. But waiting times for a cardiology consultation are still growing mainly due to chronic diseases, aging and a growing demand for prevention. Purpose: We aimed to evaluate the impact of a combined approach using digital tools and a novel outpatient team organization on access to care, in real life Methods: We implemented a full digital solution and a dedicated team in a new outpatient cardiology center (Figure). The organization was schematically divided in five parts: (1) digital PRECONSULTATION completed by the patient with an assistant and nurse support if necessary; (2) digital AI-NALYSIS of this data with a trained nurse validation to define the risk level; (3) Medical CONSULTATION either physical or using teleconsultation; (4) RESULTS: directly accessible to the patient and his GP; (5) FOLLOW-UP if relevant mainly based on digital tools and trained nurses. Activity was monitored for 9 months. The following parameters were measured: waiting time (from demand to consultation); medical efficiency (number of consultations/hour of work); patient overall satisfaction Results: 2867 consultations were performed between April and December 2019, with a waiting time of 4.3±1.6 days (compared to a national average of 61 days). Efficiency averaged 2.3 patients/hour. Patient satisfaction averaged 4.84 over 5. In addition, 160 possible consultations in the emergency room were avoided (mainly mild palpitations and non-cardiac chest pain) Conclusion: A specific digital platform and a dedicated medical team and organization improved the access to care and the medical efficiency. We believe this is a promising way to decrease the demand burden in the emergency room, to decrease the professional burnout risk and to improve prevention. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Cardioparc, Izycardio